How game phase affects the type of set used by U19, U21 and senior male beach volleyball players - Medeiros, A. I. A.; Marcelino, R.; Mesquita, I.; Palao, J.-M. (cidesd 2014 - International Congress of exercise and sports performance, 2014)
In beach volleyball, the set is the action executed to send the ball to the attacker. Senior male blockers and defenders execute the forearm more frequently to set. No information has been found in the literature related to the execution of the set in relation to player role, age group and game phase. The purpose of this study was to determine the types of set used in categories U19, U21 and senior regarding to player role and game phase. Methods A total of 348 sets (15 games) from U19, 286 sets (12 games) from U21, and 526 sets (21 games) from senior were analysed. Actions were collected from their respective World Championships (season 2010 and 2011). Sets analysed were selected randomly according to the level of the teams and their confrontation. Only sets from first and second sets of the matches were included. The variables studied were: type of set (overhead pass; forearm pass), player role (defenders; blockers), age groups (U19, U21, and senior), and game phase (K1 and K2). Data were collected through TEBEVOL (Palao & Manzanares, 2009). Data was collected by trained observer (reliability lower than 5% error). Chi-square test was used to test differences between analysed variables. Statistic significance was set at p < 0.05. Conclusion Forearm was the type of set more used. Overhead set was more used in the side-out phase. Probably due to this phase in more organize and done stable conditions. The use of the overhead set in the side-out phase increase as higher is the age group. This tendency was not found in counter-attack phase. A slightly higher used of the overhead was found by defenders. This could be influences due to defenders are shorter than blocker (Palao, Gutierrez, & Frideres, 2008), and probably had better mobility. In all the categories, blockers and defenders used more forearm pass in K2 than in K1. In senior players, in the side-out phase the use of overhead set is close to 50%. The data obtained in this study may serve as a reference for coaches to design the training process (player formation and task design) and monitor their evolution.